GEOLOGICAL STRUCTURE OF CITUNDUN AND SURROUNDING CIWARU DISTRICT, KUNINGAN REGENCY, WEST JAVA PROVINCE - Arfiansyah, Kurnia; ICHSAN, MUHAMAD; Patonah, Aton (Faculty of Geological Engineering, Universitas Padjadjaran, 2022)
Based on the Regional Geological Map of the Majenang sheet (Kastowo and Suwarna, 1996), the study area is part of the Halang Formation and the Bogor Zone (Van Bemmelen, 1949). Research conducted using the geological mapping method shows that the Citundun area and its surroundings have complex geological and tectonic structural conditions.The geological structures that develop are folds, joints and faults. The fold structure in the study area occurs during the Miocene – Pliocene transition with the main axis of the fold trending relatively northwest – southeast where from north to south, namely the Karangkancana Anticline, Kaduagung Syncline, Kaduagung Anticline, Cipari Syncline, Cipari Anticline, Sagara Syncline, Sagara Anticline, Jabranti Syncline, and Jabranti Anticline.Based on joint processing data and structural lineaments, the lineament results trending northwest-southeast and southwest-northeast. Joint structures are found in carbonate sandstones and carbonate claystones with hard and rather hard levels of hardness. In the study area, there are two strike slip fault structures, namely Sagara Sinistral Strike Slip Fault and Cipari Dextral Strike Slip Fault which are trending northeast-southwest. From the results of joint data analysis, a fault indication was withdrawn because the distribution of joint directions was supportive. Based on the regional tectonic age of West Java, during the Miocene - Pliocene the fault in the study area occurred after deposition of sandstone unit (Sbpn), carbonate claystone unit (Sblk) and carbonate sandstone unit (Sbpk) so that this fault structure is interpreted to be Pliocene in age. Referring to the concept of Moody and Hill (1956), the faults in the study area are strike slip faults of the first and second order.Keywords: Citundun, Geological Structure, Syncline, Anticline, Strike Slip Fault.